1998
DOI: 10.2323/jgam.44.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinomycin and vitamin B6 on in vitro metabolism of phenylalanine and its related compounds by ruminal bacteria, protozoa and their mixture.

Abstract: Several ionophores, such as salinomycin (SL), monensin, lasalocid, and tetronasin, have been shown to favorably alter ruminal fermentation characteristics and metabolism (Bergen and Bates, 1984;Chen and Wolin, 1979;Newbold et al., 1988;Russell and Strobel, 1989;Russell et al., 1991;Schelling, 1984). The curative effects of SL on coccidiosis (Merchen and Berger, 1985) and feedlot bloat, negative effects on the in vivo total counts of Gram-positive cocci Effects of salinomycin and vitamin B 6 on in vitro metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…BZA production from Phe by mixed rumen microorganisms (Amin et al, 1994;Scott et al, 1964) and B and P (Amin et al, 1994) were demonstrated previously, but the formation of BZA from PPY and PAA by B, P, and BP, as indicated in this experiment, is the first evidence.…”
Section: Rumen Microorganisms 13mentioning
confidence: 57%
See 4 more Smart Citations
“…BZA production from Phe by mixed rumen microorganisms (Amin et al, 1994;Scott et al, 1964) and B and P (Amin et al, 1994) were demonstrated previously, but the formation of BZA from PPY and PAA by B, P, and BP, as indicated in this experiment, is the first evidence.…”
Section: Rumen Microorganisms 13mentioning
confidence: 57%
“…In this experiment, BZA production from PAA per gram MN was 2.0-and 1.4-fold higher in P than in B and BP, respectively. The lower production of BZA from PAA in the BP suspensions was justified by mechanical calculation because B have a lower ability to produce BZA from PAA than P. The production of BZA from Phe was also higher in P in our previous report (Amin et al, 1994).…”
Section: Rumen Microorganisms 13mentioning
confidence: 96%
See 3 more Smart Citations